2014
DOI: 10.1016/s2215-0366(14)00078-9
|View full text |Cite
|
Sign up to set email alerts
|

Practice nurse health checks for adults with intellectual disabilities: a cluster-design, randomised controlled trial

Abstract: SummaryBackground Adults with intellectual disabilities have substantial health inequalities and poor access to health care. We assessed whether practice nurse-delivered health checks could improve the health of adults with intellectual disabilities compared with standard care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…We have not attempted to make any economic costing of the effectiveness of the health check scheme. A small Scottish trial of nurse delivered health checks for adults with ID demonstrated cost-effectiveness compared with standard care 17. However, they did not include hospitalisation costs, except accident and emergency attendances, which may have led to them underestimating potential economic savings.…”
Section: Discussionmentioning
confidence: 99%
“…We have not attempted to make any economic costing of the effectiveness of the health check scheme. A small Scottish trial of nurse delivered health checks for adults with ID demonstrated cost-effectiveness compared with standard care 17. However, they did not include hospitalisation costs, except accident and emergency attendances, which may have led to them underestimating potential economic savings.…”
Section: Discussionmentioning
confidence: 99%
“…The large variation in recording procedures across practices for health checks needs to be better understood to enable better cost estimates of health checks on a large scale. Both in the UK 158,159 and internationally, 160 small trials of health check intervention have suggested that there were no associated higher costs in terms of service use compared with standard care. 158,159 However, these studies may not have fully accounted for longer-term hospitalisation costs, which in turn could have led to an underestimation of any potential economic savings.…”
Section: Health Checks and Process Measuresmentioning
confidence: 99%
“…Both in the UK 158,159 and internationally, 160 small trials of health check intervention have suggested that there were no associated higher costs in terms of service use compared with standard care. 158,159 However, these studies may not have fully accounted for longer-term hospitalisation costs, which in turn could have led to an underestimation of any potential economic savings. 159 Therefore, costs implications and benefits of health checks remain unclear and require further evaluation.…”
Section: Health Checks and Process Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia and the UK, GPs are encouraged by their governments to carry out health assessments on people with ID. 17,18 GPs experience difficulties in the care of these patients. Lack of knowledge and time constraints are among the most important difficulties for GPs.…”
Section: Introductionmentioning
confidence: 99%